Comparative Evaluation of Tooth Root Channel System Damage during Pre-obturative Endodontic Processing by Physical Methods - Larinskaya, A.V. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The authors studied the effect of diode laser radiation and ultraviolet irradiation of the yellow spectrum on the structure of the root dentin during the pre-obturative sanitation/treatment of the root canal system using scanning electron microscopy. Materials and Methods: The studies were carried out in vitro on the samples of removed teeth (roots) with fibrotic changes in periodontium that had not previously undergone endodontic treatment. Results: The results of the experimental study made it possible to reveal the structural damages of solid tissues in the system of root canals during the treatment with a diode laser and the structural preservation under the action of ultraviolet irradiation. Conclusions: Thus, the physical methods of root canal sterilization at endodontic tooth treatment have a significant advantage over traditional drug processing. Moreover, irradiation with ultraviolet is a gentler method than the treatment with a diode laser.